2024
DOI: 10.3390/cells13040331
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between p-tau217, p-tau231, and p-tau205 in the Human Brain Is Affected by the Cellular Environment and Alzheimer’s Disease Pathology

Malin Wennström,
Nina Schultz,
Paula Mille Gallardo
et al.

Abstract: The levels of p-tau217 and p-tau231 in cerebrospinal fluid (CSF) are associated with early amyloid beta (Aß) changes in the brain, while the CSF levels of p-tau205 are foremost related to tau pathology in the later stages of the disease. To investigate if the three p-tau variants are found to the same degree in different tau structures and if their co-localization is affected by the diagnosis and presence of Aß plaques, we immunostained sections of the entorhinal cortex (EC) and inferior temporal gyrus (ITG) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Consequently, there is still debate regarding the best marker for AD, and new candidates are continually being proposed ( Suárez-Calvet et al ., 2020 ; Karikari et al ., 2021 ; Salvadó et al ., 2024 ). Assessing the diversity of ptau isoforms in relation to AD pathology is challenging, as these isoforms appear at different stages of AD and exhibit heterogeneous relationships with amyloid plaques and neurofibrillary tangles ( Wennström et al ., 2024 ). For instance, an earlier study comparing phosphorylation at threonine 231 (p-tau231), threonine 181 (p-tau181), and serine 199 (p-tau199) in cerebrospinal fluid (CSF) showed that ptau181 could classify AD with Lewy body dementia better than p-tau231, which differentiated AD from frontotemporal dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is still debate regarding the best marker for AD, and new candidates are continually being proposed ( Suárez-Calvet et al ., 2020 ; Karikari et al ., 2021 ; Salvadó et al ., 2024 ). Assessing the diversity of ptau isoforms in relation to AD pathology is challenging, as these isoforms appear at different stages of AD and exhibit heterogeneous relationships with amyloid plaques and neurofibrillary tangles ( Wennström et al ., 2024 ). For instance, an earlier study comparing phosphorylation at threonine 231 (p-tau231), threonine 181 (p-tau181), and serine 199 (p-tau199) in cerebrospinal fluid (CSF) showed that ptau181 could classify AD with Lewy body dementia better than p-tau231, which differentiated AD from frontotemporal dementia.…”
Section: Discussionmentioning
confidence: 99%